Marginalized Agency or Agency at the Margins: Domestic Workers and Informality - Naomi Friedman-Sokuler; Einat Lavee (Global Labor Organization (GLO), 2025)
This paper explores informality in a high income country among women who, at least legally, can take on formal jobs. Specifically, we examine the determinants of paid domestic work in Israel through the lens of existing theoretical frameworks of informality. Using rich administrative data, we identify and characterize domestic workers and their labor market histories and estimate the prevalence and degree of informality. We complement this analysis with a qualitative analysis of interviews with 144 women living in poverty, who describe their choices vis-à-vis informal employment. We find that domestic workers in Israel are best described through a conceptual framework of Marginalized Agency. For them, informal employment is not a choice of last resort but rather a site of control and agency within highly constrained life situations. Nevertheless, the structural constraints associated with informality, in turn, limit the realization of their goals, especially with respect to economic and social mobility.
Keywords: J24; J46; I30; 330; Informality; Domestic work; Poverty; Mixed methods